It is currently 24 Feb 2018, 01:37

### GMAT Club Daily Prep

#### Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History

# Events & Promotions

###### Events & Promotions in June
Open Detailed Calendar

# Data Sufficiency

Author Message
Manager
Joined: 27 Mar 2008
Posts: 64

### Show Tags

09 Aug 2008, 17:48
This topic is locked. If you want to discuss this question please re-post it in the respective forum.

Can you provide an answer with an explanation ?
Attachments

gmat ds 1.jpg [ 50.8 KiB | Viewed 1424 times ]

Director
Joined: 23 Sep 2007
Posts: 782

### Show Tags

09 Aug 2008, 20:29
C

the equation from the stem is M-J = 2(M-K)
3 unknowns

both statements together you can solve for M
VP
Joined: 17 Jun 2008
Posts: 1373

### Show Tags

10 Aug 2008, 04:44
gmatnub wrote:
C

the equation from the stem is M-J = 2(M-K)
3 unknowns

both statements together you can solve for M

IMO B
since m+j=2k and knowing kate's sal is enough
(2) suffi (1) insuffi
_________________

cheers
Its Now Or Never

Senior Manager
Joined: 06 Apr 2008
Posts: 428

### Show Tags

10 Aug 2008, 09:48
dishant007 wrote:
Can you provide an answer with an explanation ?

Let salary be x, y and z

x-y = 2(x -z)

x = 2z-y

Mean = (x + y + z)/3 = z

Therefore B is suff.
Manager
Joined: 30 Jul 2007
Posts: 130

### Show Tags

11 Aug 2008, 13:50
nmohindru wrote:
dishant007 wrote:
Can you provide an answer with an explanation ?

Let salary be x, y and z

x-y = 2(x -z)

x = 2z-y

Mean = (x + y + z)/3 = z

Therefore B is suff.

Why is Mean = (x + y + z)/3 = z ?

How did you reach z?
SVP
Joined: 07 Nov 2007
Posts: 1789
Location: New York

### Show Tags

11 Aug 2008, 20:24
sarzan wrote:
nmohindru wrote:
dishant007 wrote:
Can you provide an answer with an explanation ?

Let salary be x, y and z

x-y = 2(x -z)

x = 2z-y

Mean = (x + y + z)/3 = z

Therefore B is suff.

Why is Mean = (x + y + z)/3 = z ?

How did you reach z?

x-y = 2(x -z)

x = 2z-y

x+y=2z

(x + y + z)/3 = (2z+ z)/3=z
_________________

Smiling wins more friends than frowning

Manager
Joined: 30 Jul 2007
Posts: 130

### Show Tags

12 Aug 2008, 03:11
How did you reach z?[/quote]

x-y = 2(x -z)

x = 2z-y

x+y=2z

(x + y + z)/3 = (2z+ z)/3=z[/quote]

Thanks x2suresh
Re: Data Sufficiency   [#permalink] 12 Aug 2008, 03:11
Display posts from previous: Sort by

# Data Sufficiency

Moderator: chetan2u

 Powered by phpBB © phpBB Group | Emoji artwork provided by EmojiOne Kindly note that the GMAT® test is a registered trademark of the Graduate Management Admission Council®, and this site has neither been reviewed nor endorsed by GMAC®.